Effects of acute and repeated dosing of the synthetic cannabinoid CP55,940 on intracranial self-stimulation in mice - Grim, Travis W. (Drug Alcohol Depend, 2015)
BACKGROUND: Synthetic cannabinoids have emerged as a significant public health concern. To increase the knowledge of how these molecules interact on brain reward processes, we investigated the effects of CP55,940, a high efficacy synthetic CB(1) receptor agonist, in a frequency-rate intracranial self-stimulation (ICSS) procedure. METHODS: The impact of acute and repeated administration (seven days) of CP55,940 on operant responding for electrical brain stimulation of the medial forebrain bundle was investigated in C57BL/6J mice. RESULTS: CP55,940 attenuated ICSS in a dose-related fashion (ED50 (95% C.L.) = 0.15 (0.12–0.18) mg/kg). This effect was blocked by the CB(1) receptor antagonist rimonabant. Tolerance developed quickly, though not completely, to the rate-decreasing effects of CP55,940 (0.3 mg/kg). Abrupt discontinuation of drug did not alter baseline responding for up to seven days. Moreover, rimonabant (10 mg/kg) challenge did not alter ICSS responding in mice treated repeatedly with CP55,940. CONCLUSIONS: The finding that CP55,940 reduced ICSS in mice with no evidence of facilitation at any dose is consistent with synthetic cannabinoid effects on ICSS in rats. CP55,940-induced ICSS depression was mediated through a CB(1) receptor mechanism. Additionally, tolerance and dependence following repeated CP55,940 administration were dissociable. Thus, CP55,940 does not produce reward-like effects in ICSS under these conditions.